PENINGKATAN HASIL BELAJAR SISWA MELALUI MEDIA KOTAK SIFAT CAHAYA DI KELAS V SDN 09 PALEMBANG - Rohmi, Fathur; Suplisatyah, Esti Indah; Juherliani, Fenty; Aisyah, Nyimas; Asnaningsih, Julia (J-KIP (Jurnal Keguruan dan Ilmu Pendidikan), 2024)
The importance of understanding the concept in learning science on the material properties of light should be further enhanced because the value of understanding the concept of students is not only limited to knowing but students are also able to re-explain the material that has been taught in their own language and can apply in everyday life. Therefore, this study aims to improve the learning outcomes of students in Class V SDN 09 Palembang on the material properties of light by using Learning media Box properties of light. The method used is Class Action Research (PTK) conducted in two cycles. The study was conducted at SDN 09 Palembang on July 29, 2024 to August 5, 2024 with the subject of penelitain students of Class V SDN 09 Palembang which amounted to 28 people Data were collected through observation and tests. Observation is carried out to determine student activity during learning, while tests are carried out to determine student learning outcomes after learning. Based on the results obtained information that there is an increase in student learning outcomes that obtain high scores from Cycle 0 as much as 10.71% to Cycle 1 as much as 39.28% and Cycle 2 pretest results show that 71.42% % of students have a low understanding between 45 to 72. The results also showed an increase in student activity during learning. Although the results showed success, some students still needed additional support to understand more complex concepts. This research suggests the application of more diverse learning media and the adaptation of teaching methods to meet the individual needs of students. The use of interactive and experiment-based media allows students to see and experience firsthand the phenomenon of light, which reinforces the concepts taught. This research suggests the application of more diverse learning media and the adaptation of teaching methods to meet the individual needs of students.